Effectiveness of an Internet-Based and Telephone-Assisted Training for Parents of 4-Year-Old Children With Disruptive Behavior: Implementation Research - Andre Sourander; Terja Ristkari; Marjo Kurki; Sonja Gilbert; Susanna Hinkka-; Malin Kinnunen; Laura Pulkki-Råback; Patrick J McGrath (JMIR Publications, 2022)
BackgroundThere is a lack of effectiveness studies when digital parent training programs are implemented in real-world practice. The efficacy of the internet-based and telephone-assisted Finnish Strongest Families Smart Website (SFSW) parent training intervention on the disruptive behavior of 4-year-old children was studied in a randomized controlled trial setting in Southwest Finland between 2011 and 2013. After that, the intervention was implemented nationwide in child health clinics from 2015 onwards. ObjectiveThe main aim of this study was to compare the treatment characteristics and effectiveness of the SFSW parent training intervention between the families who received the intervention when it was implemented as a normal practice in child health clinics and the families who received the same intervention during the randomized controlled trial. MethodsThe implementation group comprised 600 families who were recruited in the SFSW intervention between January 2015 and May 2017 in real-world implementation. The RCT intervention group comprised 232 families who were recruited between October 2011 and November 2013. The same demographic and child and parent measures were collected from both study groups and were compared using linear mixed-effect models for repeated measurements. The child psychopathology and functioning level were measured using the Child Behavior Checklist (CBCL) version 1.5-5 for preschool children, the Inventory of Callous-Unemotional Traits (ICU), and a modified version of the Barkley Home Situations Questionnaire. Parenting skills were measured using the 31-item Parenting Scale and the shorter 21-item Depression, Anxiety and Stress Scale (DASS-21). The estimated child and parent outcomes were adjusted for CBCL externalizing scores at baseline, maternal education, duration of the behavior problems, and paternal age. The baseline measurements of each outcome were used as covariates. ResultsThe implementation group was more likely to complete the intervention than the RCT intervention group (514/600, 85.7% vs 176/232, 75.9%, respectively; P<.001). There were no significant differences between the implementation and RCT intervention groups with regard to child measures, including CBCL externalizing score (-0.2, 95% CI -1.3 to 1.6; P=.83), total score (-0.7, 95% CI -3.0 to 4.5; P=.70), internalizing score (-0.3, 95% CI -1.0 to 1.6; P=.64), and ICU total score (-0.4, 95% Cl -1.9 to 1.2; P=.64). No significant difference was detected in the Parenting Scale total score (0.0, 95% Cl -0.1 to 0.1; P=.50), while DASS-21 total score differed nearly significantly (2.5, 95% Cl 0.0-5.1; P=.05), indicating better improvement in the implementation group. ConclusionsThe internet-based and telephone-assisted SFSW parent training intervention was effectively implemented in real-world settings. These findings have implications for addressing the unmet needs of children with disruptive behavior problems. Our initiative could also provide a quick socially distanced solution for the considerable mental health impact of the COVID-19 pandemic. Trial RegistrationClinicalTrials.gov NCT01750996; https://clinicaltrials.gov/ct2/show/NCT01750996 International Registered Report Identifier (IRRID)RR2-10.1186/1471-2458-13-985